NaOH-Catalyzed Imine Synthesis: Aerobic Oxidative Coupling of Alcohols and Amines - Donthiri, Ramachandra Reddy; Patil, Rajendra D.; Adimurthy, Subbarayappa (European journal of organic chemistry, 2012)
The convenient transition‐metal‐free synthesis of imines through oxidative coupling of alcohols and amines is reported. The reaction is catalyzed by NaOH (10 mol‐%) and is performed with air as an oxidant in the absence of any co‐solvent. The convenient transition‐metal‐free synthesis of imines through oxidative coupling of alcohols and amines is reported. The reaction is catalyzed by NaOH (10 mol‐%) and is performed with air as an oxidant in the absence of any co‐solvent.